Participatory Action Research (PAR) with LGBTQ+ & GNC youth in the United States: An interview with Michelle Fine, Maria Torre, and Allison Cabana. - Miranda, Luciana Lobo (Revista de Psicologia, 2018)
Participatory Action Research (PAR) with LGBTQ+ & GNC youth in the United States: An interview with Michelle Fine, Maria Torre, and Allison Cabana.